Storage Stability of Fuels - Biernat, Krzysztof (IntechOpen, 2015)
This book presents an analysis of the results of studies of motor fuels ageing, conducted in laboratory and model conditions, in terms of building a system operating on-line, allowing continuous assessment of the operational usability of gasoline and diesel fuels, including those containing the addition of ethanol and FAME, respectively. This research was carried out in the framework of the project: "A system for the continuous control of the degree and rate of the liquid fuels ageing process during storage, which received co-funding from the European Regional Development Fund under the Operational Programme "Innovative Economy". The book presents an evaluation of the impact of fuel production processes on its stability and an analysis of changes in normative parameters of fuels during their storage and use. The book presents also the results of tests on the corrosive effects of fuels during storage processes. This project was co-financed by the European Regional Development Fund under the Operational Programme "Innovative Economy".